English Teachers’ Teaching Quality in Madrasah in Jakarta and Banten based on the Dynamic Model of Educational Effectiveness - Siti Nurul Azkiya (TARBIYA: Journal of Education in Muslim Society, 2015)
Abstract This paper was intended to describe English teachers’ teaching quality in teaching reading comprehension and provide some reflection and suggestion on how teaching quality could be improved. The classroom factors of the dynamic model (orientation, structuring, questioning, modeling, application, assessment, time management, and making classroom as a learning environment [CLE]) were used as a reference to conceptualize teaching quality. Classroom observation instrument was used to measure teaching quality of 59 English teachers in Madrasah Tsanawiyah in the provinces of Jakarta and Banten with a focus on reading comprehension. The findings showed that among the above eight factors, teachers rarely practiced orientation, structuring, modeling, and CLE. In addition, they did not provide enough application whereas a lot of time was spent for reading aloud and translating the text. Nevertheless, they started to raise questions and conduct assessment. With respect to questioning, however, the questions were limited to product questions, which did not promote critical thinking. Finally, the assessment method used was limited to questioning. Abstrak Tulisan ini bertujuan untuk menjelaskan kualitas guru Bahasa Inggris dalam mengajar reading comprehension dan memberikan rekomendasi strategi meningkatkan kualitas mengajar. Delapan aspek yang ada dalam the Ddynamic Model (orientation, structuring, questioning, modeling, application, assessment, time management, and making classroom as a learning environment [CLE]) dijadikan sebagai pijakan untuk mendefinisikan konsep kualitas mengajar. Penelitian ini menggunakan instrumen observasi kelas untuk melihat bagaimana guru mengajar reading comprehension. Partisipan penelitian ini adalah 59 guru Bahasa Inggris di Madrasah Tsanawiyah di propinsi DKI Jakarta dan Banten. Temuan penelitian ini menunjukkan bahwa di antara delapan aspek kualitas mengajar yang dalam the Dynamic Model, kebanyakan guru jarang sekali mempraktikkan orientation, structuring, modeling, dan CLE. Selain itu, mereka tidak banyak memberikan application dan waktu yang ada banyak terpakai untuk membaca teks dan menerjemahkannya. Meski demikian, guru-guru tersebut mulai menggunakan berbagai pertanyaan untuk memandu proses pembelajaran dan melakukan asesmen. Hanya saja, pertanyaan yang diajukan masih terbatas pada pertanyaan product yang tidak menumbuhkan daya kritis, dan metode assessmen yang dilakukan terbatas pada memberikan pertanyaan kepada siswa. How to Cite:  Azkiyah, S., N. (2015). English Teachers’ Teaching Quality in Madrasah in Jakarta and Banten Based on the Dynamic Model of Educational Effectiveness. TARBIYA: Journal Of Education In Muslim Society, 2(1), 35-46. doi:10.15408/tjems.v2i.1668. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v2i1.1668